Kinerja Karyawan Ditinjau Dari Motivasi, Disiplin Kerja dan Pengembangan Karir di Masa Pandemic Covid-19 (Studi Kasus Pada Karyawan Dinas Kesehatan Kota Surakarta di Balaikota) - Lentera Crosi Yuniati; Burhanudin Ahmad Yani; Istiqomah Istiqomah (JURNAL ILMIAH EDUNOMIKA, 2022)
This research discusses about good employee performance which is very fundamental for organizations and companies to reach a common goal, especially during the Covid-19 pandemic. The purpose of this research is to find out whether there is an influence between the variables of Motivation, Work Discipline, and Career Development on Employee Performance at The Surakarta City Health Office at City Hall simultaneously and partially. This research use quantitative research method. The population in this research include all employee of the Surakarta City Health Office at City Hall which are civil servant totaling 56 employee. Sampling using the Non Probability method using a saturated sample technique. The result of this research are that there is a simultaneous influence between motivation, work discipline, and career development on the performance employee of The Surakarta City Health Office at City Hall during the Covid-19 pandemic, while partially career development during the Covid-19 pandemic has no effect on the performance of the Departement of Health employee Surakarta City Health at City Hall.